Cosine-type weighted hybrid absorbing boundary based on the second-order Higdon boundary condition and its GPU implementation. (17th January 2020) - Xie, Chuang; Song, Peng; Tan, Jun; Liu, Baohua; Li, Jinshan; Yu, Kaiben; Zhang, Xiaobo; Zhang, Chao; Zhang, Hongyang; Zhang, Ruiqi
Abstract: In this paper, we analyze the absorption effect of the hybrid absorbing boundary condition (ABC) with various hybrid modes, and propose a cosine-type optimized weighted hybrid mode taking into account the boundary reflection intensity of the inner and outer boundaries of transition area. Additionally, we derive a new finite-difference scheme of the second-order Higdon ABC and the corner equation for Graphic Processing Unit (GPU) acceleration. On this basis, a new type of second-order Higdon hybrid ABC applicable for GPU acceleration is established in the acoustic finite-difference modeling. Numerical experiments demonstrate that the proposed cosine-type weighted hybrid mode can achieve a better absorption effect compared with other weighted hybrid modes; the second-order Higdon ABC based on the proposed new finite-difference scheme can effectively improve the GPU speed-up ratio and is more effective in large-scale wavefield high-precision simulation based on GPU acceleration.